Sound pressure radiation of a circular piston located at a two- and three-wall corners - Wojciech P. RDZANEK; Krzysztof SZEMELA; Dawid PIECZONKA (Archives of Acoustics)
This paper focuses on the far field approximation of the steady state sound pressure radiated by a flat circular piston into the region bounded by some flat rigid baffles. The two Neumann boundary value problems have been considered for the regions of two- and three-wall corners, separately. The Green function in its Fourier representation has been used together with the Sommerfeld radiation condition which has given the sound pressure approximation in the form of some useful elementary formulations. The boundary value problems often appear in the situation when the sound source is located in the vicinity of the Earth and some vertical walls, e.g. the sound barriers, the building walls, etc.